EDITORS’ NOTE (The Pretoria Student Law Review, 2021)
A sense of satisfaction is felt in presenting the seventh edition of the Pretoria Student Law Review. With each successive edition, the Review comes ever closer to being infused into the heritage and culture of the Faculty of Law at the University of Pretoria. Thereby, cementing into legacy a dialogical space for the expression of young people — some being future lawyers, advocates and academics — a space that challenges the status quo. As a consequence, the Review, as a true creature of education, may bring about positive change in the world.